Understanding sociological issues: conceptualizing the diversities - Karim, A.H.M Zehadul (IIUM Press, 2011)
UNDERSTANDING SOCIOLOGICAL ISSUES: CONCEPTUALIZING THE DIVERSITIES is an attempt to incorporate a number of existing societal issues which seem to be sociologically significant and empirically relevant. The topics chosen for this book thus contain some prolific discussion in the contemporary sociological discourse. Prudentially, the mode is a new venture to make the discipline useful to researches focusing on a few contemporary thematic issues based on diversities; this book serves to disentangle strands of thinking in an integral manifestation. The book begins with a critical thinking of theoretical sociology as it has been revealed in the Islamic perspective which is followed by another more or less sequential paper on poverty and resource inequality that prevail among the Muslim nations. Gender issues have also been dealt with significant importance by including two papers in this volume. An important and significantly inquisitive chapter on menopausal symptoms highlights the preferred menopausal treatment techniques among the urban Malay women from a medical and anthropological perspective. A chpter on the reemergence of plantation-agriculture gives clear indication that although plantation agriculture has been reemerging to make some sort of transformation in the agrarian sector, in reality, it does not help the poor as expected. The book also contains papers on social network, urban issues, social media and statutory rape as well as the work performances and socio-cultural adaptability of the Bangladeshi migrant workers. This book has brought a new diversion in the field of sociological research. Students and researchers in Sociology will undoubtedly find it useful for their future academic perseverance.